Empowerment Of PKK Group Members In West Labuh Baru Village, Pekanbaru City - Joesyiana, Kiki; Yuzalmi, Nanik; Basriani, Agustin; Susanti, Desi; Wahyuni, Sri (Doctoral Program of Social Science, Pasundan University, 2025)
The empowerment of PKK (Family Welfare Empowerment) members of Labuh Baru Barat sub-district aims to improve the abilities and roles of PKK members in many fields, such as education, economy, health and environment, so that PKK members of Labuh Baru Barat sub-district are expected to provide benefits and play an active role in building and improving the quality of society in their environment. In order to fully support community development, members of the empowerment and family welfare (PKK) driving group of Labuh Baru Barat sub-district can form a capable strategy to create a society that is both efficient and prosperous. As an organization that focuses on family welfare, members of the PKK Labuh Baru Barat group play an important role in improving the quality of life of the community through various superior programs that they have. Members of the PKK group of Labuh Baru Barat sub-district have collaborated with the village government and community institutions to make development programs a success, one of which is collaborating with community service partners from the team of lecturers from the Faculty of Economics and Business, Persada Bunda Indonesia University. Members of the PKK group of Labuh Baru Barat sub-district are also strategic partners in empowering women and families through skills training, health seminars, and other social activities. PKK often collaborates with various agencies such as the Health Service, Education Service, and Community and Village Empowerment Service (PMD). This collaboration ensures that the programs run are in line with government policies and the needs of the local community. As the vanguard in family empowerment, PKK has a major contribution in creating a healthy, prosperous, and independent society. However, maintaining all these activities is not easy. However, with the support of all parties, it is hoped that members of the PKK group in Labuh Baru Barat sub-district can continue to innovate to increase their role in sustainable development.